Constraining and supporting effects of the multilateral trading system on US unilateralism - Daniela Benavente (Graduate Institute of International and Development Studies, 2010)
The subject of this paper is Section 301 of the Trade Act of 1974 of the United States, a statute that for the past 35 years has allowed the U.S. to unilaterally handle its trade disputes. More specifically, the paper examines the constraining and supporting effects of the multilateral trading system (GATT and WTO) on the effectiveness of Section 301 in general (127 cases), and of retaliatory threats and sanctions in particular (44 cases). In contrast with previous empirical papers, the emphasis is on the gradual interaction between both instances, with special attention to the escalation of the multilateral dispute and the timing of retaliatory threats and sanctions (if any). The paper shows that contrary to conventional wisdom, Section 301 has been less about aggressive unilateralism (Bhagwati and Patrick 1991) than about reinforcing the multilateral trading system and the U.S. agenda in it. Section 301 proceedings and retaliation were often used in contravention of international trade law; but they were also used as tools to enforce multilateral rulings or to advance the multilateral agenda upon non-Members or on new issues. To address the effectiveness question, a qualitative response model is used. Results confirm the hypothesis prevalent in the extant literature that a process of escalation at the GATT/WTO is correlated with a higher success rate of Section 301 investigations in changing the target country's policy. However, the impact is not linear; a settlement is more likely early in the bargaining stages rather than after a ruling is issued by a GATT/WTO panel. The empirical estimation is based on a comprehensive dataset on all Section 301 cases and on the related GATT/WTO dispute(s); and on 45 case studies outlined in the Appendix which, supplemented by the case studies of Bayard & Elliott (1994), are the basis for the coding of the dependent variable.
Keywords: 330; WTO-Regeln; Außenwirtschaftspolitik; USA; Handelskonflikt; Internationale Schiedsgerichtsbarkeit; Internationale Handelspolitik; Welt